Lanthanide(III) Chelates of DTPA Bis(amide) Glycoconjugates: Potential Imaging Agents Targeted at the Asyaloglycoprotein Receptor - Baía, Paula (2005)
The synthesis and characterisation of a new class of DTPA bis(amide) linked glycoconjugates of different sugars [lactose (Lac) and galactose (Gal)] and valencies (di and tetra) and their LnIII complexes is reported. The 1H NMR spectra of the SmIII and EuIII complexes of DTPAGal2, DTPAGal4, and DTPALac2, obtained between 7 and 80 °C, indicate that several of the four possible diastereoisomeric pairs of structures resulting from the chirality of the three bound DTPA nitrogen atoms are present in solution, with different relative populations. The dynamic effects of racemisation of the central nitrogen atom in the NMR spectra show that this process is fast at 60 °C for the SmIII complexes and slow at 7 °C for the EuIII complexes. The in vitro r1 nuclear magnetic relaxation dispersion (NMRD) of the water protons of the GdIII-DTPA bis(amide) glycoconjugate containing two lactosyl moieties [GdIII-DTPALac2] was studied, yielding the molecular parameters that govern its relaxivity. Its r1 value, at 25 °C and 20 MHz, is 13 % higher than that reported for GdIII chelates of lower molecular weight DTPA bis(amides), such as DTPA-BMA, consistent with a five times larger tauR value. The water exchange rate, kex, and the electron spin relaxation parameters of the GdIII-DTPALac2 complex are within the usual range for similar GdIII-DTPA bis(amide) chelates. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2005)